2016
DOI: 10.2308/jmar-51476
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Eco-Control Package on Environmental and Economic Performance: A Natural Resource-Based Approach

Abstract: While a growing body of literature has examined and demonstrated the influence of eco-control on organizational performance, little is known about how this influence occurs within the organization. Building on a natural resource-based view, the aim of this study is to investigate the extent to which the eco-control package supports environmental capabilities that, in turn, contribute to an organization's environmental and economic performance. Using survey data from a sample of Canadian manufacturing firms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
137
1
21

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(180 citation statements)
references
References 97 publications
21
137
1
21
Order By: Relevance
“…Epstein and Roy () bridged the gap between CS formulation and implementation which requires translating formulation into action. In addition, Journeault () suggested that eco‐control packages promote the generation of new environmental innovative capabilities, such as eco‐learning, environmental invention, stakeholder incorporation, and shared environmental perception and in turn improves corporate performance. This finding is supported by the development of appropriate plans and performance indicators (Braam, de Weerd, Hauck, & Huijbregts, ; Szekely & Knirsch, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Epstein and Roy () bridged the gap between CS formulation and implementation which requires translating formulation into action. In addition, Journeault () suggested that eco‐control packages promote the generation of new environmental innovative capabilities, such as eco‐learning, environmental invention, stakeholder incorporation, and shared environmental perception and in turn improves corporate performance. This finding is supported by the development of appropriate plans and performance indicators (Braam, de Weerd, Hauck, & Huijbregts, ; Szekely & Knirsch, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to face these challenges, some of the literature has addressed the importance of developing strategic tools that integrate environmental issues into a firm's core business approach, linking environmental aspects to the corporate strategy (e.g., Länsiluoto and Järvenpää, ; Searcy, ; Journeault and De Rongé, ). Eco‐control has been identified as one of the mechanisms that can help firms tackle environmental challenges (e.g., Judge and Douglas, ; Henri and Journeault, ; Arjaliès and Mundy, ; Epstein and Buhovac, ).…”
mentioning
confidence: 99%
“…Past research has demonstrated that eco‐control may play an important role in supporting the adoption and deployment of environmental strategy within organizations (e.g., Epstein and Buhovac, ; Gond, Grubnic, and Herzig, ; Pondeville and Swaen, ; Arjaliès and Mundy, ; Journeault and De Rongé, ). The literature highlights the ways in which eco‐control helps identify environmental issues and opportunities and fosters the establishment of environmental strategic priorities and goals (e.g., Epstein, ; Epstein and Bichard, ; Arjaliès and Mundy, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations